Find the following indefinite integral. Express your answer in exact form. Simplify.?
ln (radical 2) to 0
(e^x)/ ( radical (4-e^(2x) ) dx
ln (radical 2) to 0
(e^x)/ ( radical (4-e^(2x) ) dx
Captain Matticus, LandPiratesInc
e^(x) * dx / sqrt(4 - e^(2x))
4 - e^(2x) = 4 - 4 * sin(t)^2
e^(2x) = 4 * sin(t)^2
e^(x) = 2 * sin(t)
e^(x) * dx = 2 * cos(t) * dt
e^(x) * dx / sqrt(4 - e^(2x)) =>
2 * cos(t) * dt / sqrt(4 - 4 * sin(t)^2) =>
2 * cos(t) * dt / sqrt(4 * cos(t)^2) =>
2 * cos(t) * dt / (2 * cos(t)) =>
dt
Integrate
t + C
e^(x) = 2 * sin(t)
(1/2) * e^(x) = sin(t)
t = arcsin((1/2) * e^(x))
arcsin((1/2) * e^(x)) + C
From 0 to ln(2^(1/2))
arcsin((1/2) * e^(ln(2^(1/2))) - arcsin((1/2) * e^(0)) =>
arcsin((1/2) * 2^(1/2)) - arcsin((1/2) * 1) = >
pi/4 - pi/6 =>
3pi/12 - 2pi/12 =>
pi/12
Anonymous
int_[-sqrt(2)]^(0) (e^x)/sqrt[4 - (e^(2x))] dx
u = e^x; du = e^x dx; a = e^(-sqrt(2)); b = 1
int_[e^(-sqrt(2))]^(1) 1/sqrt(4 - (u^2)) du
u = 2*sin(t); du = 2*cos(t) dt; a = arcsin[e^(-sqrt(2))/2]; b = pi/6
int_{arcsin[e^(-sqrt(2))/2]}^(pi/6) [2*cos(t)/sqrt(4 - 4*sin^2(t))] dt
int_{arcsin[e^(-sqrt(2))/2]}^(pi/6) [2*cos(t)/(2*cos(t))] dt
int_{arcsin[e^(-sqrt(2))/2]}^(pi/6) dt
http://www.wolframalpha.com/input/?i=int_%7Barcsin%5Be%5E(-sqrt(2))%2F2%5D%7D%5E(pi%2F6)+dt